2016
DOI: 10.1002/2016gl071438
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotopes of hydrogen to quantify biogenic and thermogenic atmospheric methane sources: A case study from the Colorado Front Range

Abstract: Global atmospheric concentrations of methane (CH4), a powerful greenhouse gas, are increasing, but because there are many natural and anthropogenic sources of CH4, it is difficult to assess which sources may be increasing in magnitude. Here we present a data set of δ2H‐CH4 measurements of individual sources and air in the Colorado Front Range, USA. We show that δ2H‐CH4, but not δ13C, signatures are consistent in air sampled downwind of landfills, cattle feedlots, and oil and gas wells in the region. Applying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…A few other studies that have apportioned (Peischl et al, 2018;Petron et al, 2014;Townsend-Small et al, 2016) or quantified (Eilerman et al, 2016;Fried et al, 2015;Gilman, 2017;Tzompa-Sosa et al, 2017;Yuan et al, 2017) CH 4 in the DJB study area exist, but none have attempted to source apportion CH 4 based on excess columns. These results can be used to assess how the concept of excess columns compares with results based on in situ observations.…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A few other studies that have apportioned (Peischl et al, 2018;Petron et al, 2014;Townsend-Small et al, 2016) or quantified (Eilerman et al, 2016;Fried et al, 2015;Gilman, 2017;Tzompa-Sosa et al, 2017;Yuan et al, 2017) CH 4 in the DJB study area exist, but none have attempted to source apportion CH 4 based on excess columns. These results can be used to assess how the concept of excess columns compares with results based on in situ observations.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…These results can be used to assess how the concept of excess columns compares with results based on in situ observations. The data by Townsend-Small et al (2016) remain somewhat ambiguous whether the majority of CH 4 is from NG or agriculture. The attribution to NG agrees well with values reported in studies by Petron et al (2014) for Weld County in May 2012 and Peischl et al (2018) as shown in Table 1, where the dominating source of CH 4 is determined to be the NG sector.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Average enhancements of CH 4 were similar for both periods (July: 52 ppbv; August: 50 ppbv; or ∼ 2.5 % increase). Methane has a relatively high background at BAO due to large emissions of CH 4 in nearby Weld County from livestock production and oil and gas development (Pétron et al, 2014;Townsend-Small et al, 2016). Taken together, the larger background of CH 4 and the large local sources of CH 4 in the Front Range served to mute the impact of the August smoke on overall CH 4 abundances.…”
Section: Smoke Eventsmentioning
confidence: 99%
“…(iii) Source signatures could also exhibit temporal variation due to changing emission processes. Examples of 10.1029/2018GB006065 Global Biogeochemical Cycles temporal variation include changing oil and gas extraction depths within a producing basin over time (Townsend-Small et al, 2016), or wetland methanogenesis at a given location changing due to changing environmental conditions (McCalley et al, 2014). For all sources, measurements assessing temporal source signature variability are more limited than those assessing spatial variability.…”
Section: Isotopic Ratio Measurementsmentioning
confidence: 99%